ANTIOXIDANT ACTIVITY OF RED DRAGON FRUIT PEEL (HYLOCEREUS POLYRHIZUS (F.A.C. WEBER) BRITTON AND ROSE) ISOLATES USING 2,2-DIPHENYL-1-PICRYLHYDRAZYL METHOD - Wahdaningsih, Sri; Wahyuono, Subagus; Riyanto, Sugeng; Murwanti, Retno (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Â Objective: Indonesia is a country which has various natural resources including medicinal plants. Among the plants, red dragon fruit is interesting to be studied. In this study, antioxidant activity of red dragon fruit peel (Hylocereus polyrhizus (F.A.C. Weber) Britton and Rose) isolate was tested using 2,2-diphenyl-1-picrylhydrazyl method. Methods: Isolation of active compounds was performed through the application of vacuum liquid chromatography and preparative thin-layer chromatography (TLC). Antioxidant activity was tested using both TLC and spectrophotometry. Result: Results revealed that the values of IC50 of isolate 1 and 2 were 2.952, 14 Î¼g/mL and 25.635,95 Î¼g/mL, respectively. Conclusion: Isolate of dragon fruit has antioxidant activity. The compound which results in antioxidant activity is terpenoid and steroid.